A Rare Case of Acute Pulmonary Embolism after Coronary Angiography due to Sand Bag Compression - Kivrak, Tarik; Durmus, Erdal; Atas, Halil; Sunbul, Murat; Sari, Ibrahim (International Journal of Angiology, 2013)
Pulmonary embolism (PE) is very rare after coronary angiography. We present here a case of acute PE after coronary angiography due to sand bag compression which has not been reported previously. After the femoral sheath removal, patient was immobilized for 6 hours with a sand bag on his right femoral artery area. After the removal of sand bag, patient stood up with the help of a nurse. Immediately after standing up, patient complained sudden onset of dyspnea, lost his consciousness, and suddenly fell on the ground while hitting left occipital region of his head. Clinical, echocardiographic, laboratory, and tomographic findings were compatible with massive PE and we decided to give thrombolytic agent. On the contrary, because he had cranial trauma during syncope and oozing type hemorrhage in his right inguinal region, we administered a total dose of 50 mg alteplase (tissue plasminogen activator) within 2 hours (normal recommended dose is 100 mg). Just after finishing alteplase, clinical, laboratory, and echocardiographic parameters of the patient returned to normal without any complication. Patient was discharged with warfarin treatment 5 days after the event.
Keywords: pulmonary embolism; sand bag; venous compression; coronary angiography